Illegible : A Novel - Gandlevskiĭ, Sergeĭ (Book collections on Project MUSE., 2019)
"First English translation of a prose novel by an acclaimed Russian poet. Set in Moscow in the 1970's, the novel follows a group of bohemian poets in both first and third person narratives"--